Cities as sustainable ecosystems: principles and practices - Newman, Peter; Jennings, I. (Island Press, 2008)
In the early years of the new millennium humankind faces the challenge of moving onto a more sustainable path. Cities, now home to almost half of humanity, are growing faster than ever before in human history. While cities provide expanding economic opportunities in the new global economy, they are also big contributors to environmental disruption both within and well beyond their boundaries, and many are experiencing growing social problems. Thus, cities have a critical role to play in achieving sustainability. Cities as Sustainable Ecosystems (CASE) offers a way forward. The central notion is that the best innovations in human history have arisen by learning from and modelling natural systems. Cities need to develop this perspective. The ecosystem viewpoint is an inclusive one that sees humans as part of social-ecological systems - local ecosystems through bioregions to the biosphere - where the focus is on relationships and processes which support life in its myriad forms, especially partnerships and cooperation